PENGUATAN PEMBINAAN NARAPIDANA SEBAGAI UPAYA MENCEGAH KEJAHATAN” LEMBAGA PEMASYARAKATAN “SEKOLAH - Lonna Yohanes Lengkong; Toga Lamhot Sinaga (GEVANGENEN Jurnal Pemasyarakatan, 2025)
The phenomenon of correctional institutions being perceived as “schools of crime” arises from interactions among recidivist inmates that may reinforce criminal behavior. The research problem focuses on identifying the characteristics and impacts of prisonization, as well as evaluating the effectiveness of inmate rehabilitation in preventing such stigma. The study employs a normative and empirical legal approach, analyzing correctional regulations alongside the social realities of inmates. Theoretical frameworks used include the concepts of prisonization, corrections as social rehabilitation, and corrective criminal law. The findings indicate that inmate rehabilitation requires strengthening through the enhancement of rights, facilities, vocational education, and the involvement of communities and the workforce to reduce the negative effects of incarceration. Conclusion: It is essential to emphasize that integrating rehabilitation programs with community participation is crucial to eliminating the “school of crime” stigma and supporting the healthy social reintegration of inmates—transforming them from mere subjects of punishment into empowered correctional residents.